Liver iron overload and hepatic function in children with thalassemia major - Pustika Amalia Wahidiyat; Stephen Diah Iskandar; Ludi Dhyani Rahmartani; Damayanti Sekarsari (Indonesian Pediatric Society, 2018)
Background Routine blood transfusions and increased intestinal iron absorption lead to iron accumulation in various organs, especially the liver. To date, T2-star magnetic resonance imaging (T2*MRI) is a valuable tool to evaluate iron level in organs. Objective To assess the degree of liver iron overload among children with thalassemia major (TM) and its possible correlations with hepatic function laboratory values. Methods This cross-sectional study was conducted in Cipto Mangunkusumo Hospital. The degree of liver iron overload was evaluated by T2*MRI. Assessments of serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), albumin, and bilirubin levels were done to evaluate liver function. Results A total of 291 TM children were included in this study. The mean age of subjects was 12 years. Most of the subjects were diagnosed as Î²-thalassemia homozygote (54.6%) and Î²-thalassemia/HbE (41.2%). Deferiprone (DFP) was the most commonly used iron chelator. Less than 10% of the subjects had normal liver iron deposition. The AST and ALT values increased proportionally with the severity of liver iron overload, with significant, moderately negative correlation coefficients (r=-0.388 and -0.434, respectively). However, albumin level decreased proportionally with the severity of liver iron overload, with a significant, moderately positive correlation coefficient (r=0.323). Liver T2* MRI had no significant correlations with direct, indirect, and ratio of direct/total bilirubin levels. Conclusion Most of the children with TM have mild to severe liver iron overload. Liver T2* MRI had significant, moderate correlations with AST, ALT, and albumin values. Bilirubin level has no correlation with T2* MRI. Our findings suggest that monitoring of AST, ALT, and albumin levels is important because they may reflect the severity of liver iron overload. However, they should not be used as the only predictors of iron overload.